Kecemasan Dalam Public Speaking (Studi Kasus Pada Presentasi Makalah Mahasiswa) - . Aryadillah (Cakrawala - Jurnal Humaniora, 2017)
The ability of communicators in conveying information in public, had to be considered. Speaking style, body language, to the psychological state of the communicator, be a part that needs to be well prepared. Feelings of anxiety, worry, or commonly known as stage fright, often occurs when the communicator is in front of the audience. Similarly, the psychological condition of students when doing a presentation in front of the audience often experience anxiety in the presentation, as well as what causes the anxiety that happens, and how to cope with down syndrome? This has been a study in this research study. The methodology in this study using a case study with a qualitative approach. The results of this judging, namely; (1) Psychologically, individuals who are dealing directly with the audience, is certainly experiencing anxiety. (2) The cause of communicators who have Down syndrome is the lack of preparation. (3) The way to overcome this communication apprehension, is to prepare the material that will be presented carefully so as to overcome the “attacking psychology”  Keyword: Anxiety, Public Speaking, Presentation Paper.